Global Outlook on the Meat Market and Alternatives: Plant-Based and Cultivated Meat Challenges, Developments, and Opportunities. - ANJUM, MURSALEEN; KHAN, MURTAZA; KHALID, SUMMRA; ALI, NISAR; AL-HINAAI, MOHAMMAD MUSABAH (Current Research in Nutrition & Food Science, 2026)
The global food system is undergoing a significant transformation, driven by escalating concerns over environmental sustainability, animal welfare, and public health. Also, the growing demand for protein and the impacts of traditional meat production drive the need for alternative protein markets. Plant-based meat is starting to look like a good choice. This article investigates the commercial viability of the meat market and plant-based meat alternatives. It compares alternative protein products to traditional beef options, highlighting their relative benefits and trade offs. Furthermore, this paper provides a comprehensive analysis of the contemporary meat market and its two most prominent alternatives: plant-based meat and lab-grown (cultivated) meat. The key challenges and opportunities that will shape future market growth, as well as constraints such as high prices and consumer acceptance barriers. We also explore how the Product, Price, Place, and Promotion can be leveraged to unlock opportunities and drive growth in the meat substitute industry.